An empirical examination of online restaurant reviews on Yelp.com: A dual coding theory perspective. Issue 2 (13th February 2017) - Yang, Sung-Byung; Hlee, Sunyoung; Lee, Jimin; Koo, Chulmo
Abstract : Purpose: The purpose of this study is to explore the effect of two types of presentation formats (textual and imagery) involving online restaurant reviews (ORRs). The study examines ORRs on the basis of review usefulness and review enjoyment; the study investigates the effects of the two presentation formats on review usefulness and review enjoyment. Design/methodology/approach: Data from 1, 776 reviews were collected from Yelp.com using a Web data-harvesting technique. Hypothesized relations in the model were tested by Tobit regression analysis. Findings: Empirical results show that different formats of ORRs affect review usefulness and review enjoyment in different manners; whereas both attributes of textual format (review length and readability) affect review usefulness, both aspects of imagery format (physical environment images and food and beverage images) are positively related to review enjoyment. However, review length and food and beverage images are the most important factors affecting both review usefulness and review enjoyment. In particular, the relation between the two formats of ORRs and review usefulness is mediated by review enjoyment. Research limitations/implications: The focus of this study is the two formats of ORRs in terms of dual coding theory and the mediating role of review enjoyment. The findings help online review website organizers manage the operation of various review formats in a proper manner. Managers can effectively select those formats that would achieve the desired effect. Originality/value: Unlike previous studies on the relation of attributes to online reviews, this study examines the perceptions of ORRs' usefulness and enjoyment. In addition, this study encompasses diverse ORR factors (review length, review readability, physical environment images, food and beverage images) for a more comprehensive interpretation of ORRs.